STUDI KASUS PENERAPAN KODE ETIK JURNALISTIK PADA BERITA SIBER YANG DIBAGIKAN MELALUI GRUP FACEBOOK “METRO BALI” - Kadek Wiramarta (Universitas Pendidikan Ganesha, 2017)
This research is aimed at knowing (a) the sinchronization of the news spread by facebook group Metro Bali with the Ethic Code of Journalistics and (b) awareness level of social media users in Bali about journalism’s news standard in the form of Ethic Code of Journalistics. To achieve this goal, 35 cyber news in “Metro Bali” was used by using purposive sampling technique. Other than that, there are 62 social media users chosen by random sampling technique. On this research, news cyber media in facebook group “Metro Bali” was observed by using checklist of Ethic Code of Journalistics as instruments. The comments on news sample were also observed to see the reaction of social media users on the shared cyber news. Other than that, social media users are given questionnaires. The collected data were analyzed quantitatively and qualitatively. The result of this research shows that (a) there are still many news that haven’t met the standards of Ethic Code of Journalistics and (b) there are still many social media users who haven’t tried to synchronize the news’ contents with the Ethic Code of Journalistics. This research is expected at improving the society’s awareness to be wise social media readers and users especially on the issue of cyber news